Flavonoids and Their Glycosides as Anti‐amyloidogenic Compounds: Aβ1–42 Interaction Studies to Gain New Insights into Their Potential for Alzheimer's Disease Prevention and Therapy. Issue 1 (5th December 2016) - Guzzi, Cinzia; Colombo, Laura; Luigi, Ada De; Salmona, Mario; Nicotra, Francesco; Airoldi, Cristina
Abstract: Combining NMR spectroscopy, transmission electron microscopy, biochemical and in vitro toxicity assays, we characterized the effect of flavonoid glycosylation, a chemical modification found very frequently in nature, on their ability to recognize and bind Aβ1–42 oligomers, preventing their aggregation and their neurotoxicity. Our data allow the elucidation of their structure–activity relationships, showing that glycosylation has a modest impact on flavonoid affinity for Aβ oligomers but, at the same time, increases both solubility and chemical stability, thus promoting their beneficial properties against Alzheimer's disease (AD). As flavonoids and their glycosides are widely available in natural foods, our results provide important information for the evaluation of the role of a flavonoid‐rich diet for the prevention of AD. In addition, the structural data collected can be exploited for the rational design of more potent Aβ oligomer inhibitors, useful for the development of new therapies against AD. Abstract : Recognize each other : Combining NMR spectroscopy, transmission electron microscopy, biochemical and in vitro toxicity assays, the effect of flavonoid glycosylation, a chemical modification found very frequently in Nature, on their ability to recognize and bind Aβ1–42 oligomers, preventing their aggregation and their neurotoxicity, was characterized.